2007
DOI: 10.4141/cjps06014
|View full text |Cite
|
Sign up to set email alerts
|

Weed control, environmental impact and profitability of reduced rates of imazethapyr in combination with dimethenamid in dry beans

Abstract: Soltani, N., Van Eerd L. L., Vyn, R. J., Shropshire, C. and Sikkema P. H. 2007. Weed control, environmental impact and profitability of reduced rates of imazethapyr in combination with dimethenamid in dry beans. Can. J. Plant Sci. 87: 671-678. Field experiments were conducted from 2003 to 2005 in Ontario to determine if reduced rates of imazethapyr (< 75 g a.i. ha -1 ) tank-mixed with dimethenamid applied preemergence (PRE) can be used as a feasible weed management strategy for broad-spectrum weed control in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Only 22% or less of the MRR for dimethenamid plus dicamba/atrazine and nicosulfuron/rimsulfuron plus dicamba/diflufenzopyr was sufficient to provide yields at 95% of the weedfree check. These results are similar to those of other studies that have shown that herbicide rates can be reduced as much as 15 to 90% of the MRR without any significant yield losses in corn under some environmental conditions (Forcella 1995;Hamill and Zhang 1995;Weide et al 1995;Schans and Weide 1999;Alm et al 2000;Zhang et al 2000;Hamill et al 2004). However, other research has shown yield reductions of 10 to 15% in corn under some environmental conditions when nicosulfuron plus rimsulfuron was tank-mixed with other herbicides at 25% of MRR (Sikkema et al 2007).…”
Section: Yieldsupporting
confidence: 81%
See 1 more Smart Citation
“…Only 22% or less of the MRR for dimethenamid plus dicamba/atrazine and nicosulfuron/rimsulfuron plus dicamba/diflufenzopyr was sufficient to provide yields at 95% of the weedfree check. These results are similar to those of other studies that have shown that herbicide rates can be reduced as much as 15 to 90% of the MRR without any significant yield losses in corn under some environmental conditions (Forcella 1995;Hamill and Zhang 1995;Weide et al 1995;Schans and Weide 1999;Alm et al 2000;Zhang et al 2000;Hamill et al 2004). However, other research has shown yield reductions of 10 to 15% in corn under some environmental conditions when nicosulfuron plus rimsulfuron was tank-mixed with other herbicides at 25% of MRR (Sikkema et al 2007).…”
Section: Yieldsupporting
confidence: 81%
“…Some researchers have found adequate weed control and improved economic returns when herbicides are reduced 50 to 70% of the MRR (Forcella 1995;Hamill and Zhang 1995;Schans and Weide 1999). Other studies have shown that under some environmental conditions, herbicide rates can be reduced as much as 80 to 90% without a significant loss in the yield of corn (Weide et al 1995;Alm et al 2000).…”
mentioning
confidence: 99%
“…Similarly, Chomas & Kells (2004) found that pendimethalin provided greater (98%) and more consistent control of common lambsquarters in maize (Zea mays L.) than metolachlor (66%). Soltani et al (2007) also found poor control of common lambsquarters by the chloroacetamide dimethenamid applied in kidney beans, while Kantar et al (1999) reported satisfactory control of this weed by the urea linuron or by the imidazolinone imazethapyr applied in preemergence in chickpea.…”
Section: Weeds Presencementioning
confidence: 99%
“…The impact of a specific herbicide is determined by taking the EIQ of the herbicide and multiplying it by the application rate; the lower the number, the lower the EI of the herbicide (Edwards-Jones and Howells 2001; Kovach et al 1992Kovach et al , 1999. The EIQ has been used by various researchers to determine the environmental risks of various weed management strategies (Brimner et al 2005;Edwards-Jones and Howells 2001;Fernandez-Cornejo 1998;Gallivan et al 2001;Sikkema et al 2007;Soltani et al 2007). The EIQ allows researchers as well as applicators to make a more informed decision on the potential environmental impact of the herbicide being used.…”
mentioning
confidence: 99%